2012
DOI: 10.1007/s11606-011-1975-3
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Drug Use and Mortality Outcomes Among Adults Followed Over 18 Years

Abstract: BACKGROUND: For adults in general population community settings, data regarding long-term course and outcomes of illicit drug use are sparse, limiting the formulation of evidence-based recommendations for drug use screening of adults in primary care. OBJECTIVE: To describe trajectories of three illicit drugs (cocaine, opioids, amphetamines) among adults in community settings, and to assess their relation to all-cause mortality. 1987/88, 1990/91, 1992/93, 1995/96, 2000/01, 2005/ 06. Survey-based assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…As regards the injecting drug use, the studies reported in the literature confirm a higher risk of death for these subjects, also in relation to the low age at the start of drug taking, high dosages, consumption intensity, duration of the addiction, high age of initial contact with the health care services and for the subjects with a history of incarceration, low education levels, jobless, use of alcohol and other drugs, high levels of ill-health, risk behavior, social exclusion, and marginalization (Arendt, 2011;Gossop, Griffiths, Powis, Williamson, & Strang, 1996;Hickman et al, 2003;Kertesz et al 2012).…”
Section: Discussionmentioning
confidence: 64%
“…As regards the injecting drug use, the studies reported in the literature confirm a higher risk of death for these subjects, also in relation to the low age at the start of drug taking, high dosages, consumption intensity, duration of the addiction, high age of initial contact with the health care services and for the subjects with a history of incarceration, low education levels, jobless, use of alcohol and other drugs, high levels of ill-health, risk behavior, social exclusion, and marginalization (Arendt, 2011;Gossop, Griffiths, Powis, Williamson, & Strang, 1996;Hickman et al, 2003;Kertesz et al 2012).…”
Section: Discussionmentioning
confidence: 64%
“…Less severe substance use is associated with cancer risk, poor hypertension control, and worse mental health. 20,21 Less severe substance use is particularly significant for homeless persons, who are at greater risk of falls and injuries. 50 Persons with past problematic use, especially with ongoing use of other substances, incur risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…A form of multivariate mixture modeling, this method uses PROC TRAJ (Jones et al, 2001) in SAS (SAS Institute Inc., 2008) and has proven helpful in understanding other substance use patterns longitudinally (Caldeira et al, 2012a; Caldeira et al, 2012b; Jackson et al, 2005; Kertesz et al, 2012; Suerken et al, 2016). We tested all one- to seven-group solutions with a second-degree polynomial in a series of three alternative sets of analyses.…”
Section: Methodsmentioning
confidence: 99%